(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the Trabecular Bone Score (TBS) and the risk of major and hip fractures using FRAX ™ Brazil adjusted by TBS in postmenopausal women with type 2 Diabetes Mellitus. Materials and Methods: Cross-sectional study carried out in the bone densitometry (DXA) sector of a private clinic. A table of 124 women who underwent DXA and trabecular bone score (TBS) were eligible for the study. They were grouped into the Control Group (CG) without DM2 and the Diabetes Group (GD) with DM2, matched for age, weight and height. Results: The most frequent clinical characteristics were secondary osteoporosis and previous fracture. Among the fractures, the forearm was the most common site of fracture. Mean TBS was higher in Control Group: CG = 1.338 ± 0.08 vs GD 1.279 ± 0.1 p < 0.002. FRAX™ Brazil adjusted by TBS detected a higher risk for fractures in the Diabetes Group. There was a negative correlation between age and TBS in both groups (r = -0.25 p < 0.004). Conclusion: The use of TBS and TBS-adjusted FRAX® Brazil in postmenopausal women with type 2 diabetes was able to identify lower TBS and higher fracture risk even in individuals without a densitometric diagnosis of osteoporosis.